Characterisation of Uranophane and Boltwoodite by Raman, luminescence and laser-induced breakdown spectroscopy. (March 2022) - Frankland, Victoria L.; Rickman, Sam P.; Milodowski, Antoni E.; Read, David
Abstract: Among the wide range of spent nuclear fuel alteration products, uranophane-type uranyl silicates have attracted particular attention due to their ability to incorporate additional ions into their crystal structures, including other radionuclides. Two such mineral phases, uranophane ( s.s. ) (Ca(UO2 )2 (SiO3 OH)2 ·5(H2 O)) and boltwoodite ((K, Na)(UO2 )(SiO3 OH)·1.5H2 O), have been characterised by Raman, luminescence and laser-induced breakdown spectroscopy. Well-defined Raman features were observed in each case with the two minerals being differentiated by detection of the ν 3 (SiO4 ) 2- and δ (SiOH) modes for uranophane but not boltwoodite. Some distinction between uranophane-α and -β was observed by Raman, but the phase sensitivity was more apparent in the luminescence emission peak positions. The luminescence signal emitted for boltwoodite was much weaker than with uranophane, suggesting that the associated K + and Na + cations in the former are more efficient at chemical quenching than Ca 2+ . This study also reports the first luminescence excitation data for uranophane and boltwoodite. Graphical abstract: Image 1 Highlights: Characterisation of Uranophane and Boltwoodite by Raman, Luminescence and Laser-Induced Breakdown Spectroscopy - Highlights. Uranophane and boltwoodite are potential alteration products of spent nuclear fuel. Mineral specimens were characterised LIBS, Raman and luminescence spectroscopy. Luminescence emission peak positions can discriminate between uranophane polymorphs. First reported luminescence excitation spectra for uranophane and boltwoodite.